2020
DOI: 10.21203/rs.3.rs-118716/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety and Facial Self-Contacts as Risk Factors for COVID-19 in Dental Practice.

Abstract: Background: This study makes innovative contributions regarding the association of facial self-contact frequency and duration in dental clinic patients with psychosocial factors such as dental fear, fear of COVID-19 and trait anxiety, because such self-contact could have an impact on the transmission of SARS-CoV-2.Results: Statistically significant associations were found between the number and duration of facial self-contacts with trait anxiety and dental fear. Women showed more frequent self-contact of the f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous research findings indicate that sFST occur more frequently when negative emotions, such as anxiety, tension, discomfort, or insecurity, are evoked (Carrillo-Díaz et al, 2020;D'Alessio & Zazzetta, 1986;Goldberg & Rosenthal, 1986;Harrigan, 1985;Knöfler & Imhof, 2007;Moszkowski & Stack, 2007). Recent studies have shown a positive association between trait anxiety and the number of sFST (Carrillo-Díaz et al, 2020;Carrillo-Díaz et al, 2021). In this context, emotion-regulating functions are attributed to sFST (D'Alessio & Zazzetta, 1986;Grunwald et al, 2014;Harrigan, 1985;Moszkowski & Stack, 2007;Mueller et al, 2019;Reissland, Aydin, et al, 2015a;Reissland, Francis, et al, 2015b).…”
Section: Trigger Mechanisms and Functional Aspects Of Spontaneous Fac...mentioning
confidence: 96%
See 2 more Smart Citations
“…Previous research findings indicate that sFST occur more frequently when negative emotions, such as anxiety, tension, discomfort, or insecurity, are evoked (Carrillo-Díaz et al, 2020;D'Alessio & Zazzetta, 1986;Goldberg & Rosenthal, 1986;Harrigan, 1985;Knöfler & Imhof, 2007;Moszkowski & Stack, 2007). Recent studies have shown a positive association between trait anxiety and the number of sFST (Carrillo-Díaz et al, 2020;Carrillo-Díaz et al, 2021). In this context, emotion-regulating functions are attributed to sFST (D'Alessio & Zazzetta, 1986;Grunwald et al, 2014;Harrigan, 1985;Moszkowski & Stack, 2007;Mueller et al, 2019;Reissland, Aydin, et al, 2015a;Reissland, Francis, et al, 2015b).…”
Section: Trigger Mechanisms and Functional Aspects Of Spontaneous Fac...mentioning
confidence: 96%
“…Previous research findings indicate that sFST occur more frequently when negative emotions, such as anxiety, tension, discomfort, or insecurity, are evoked (Carrillo-Díaz et al, 2020;D'Alessio & Zazzetta, 1986;Goldberg & Rosenthal, 1986;Harrigan, 1985;Knöfler & Imhof, 2007;Moszkowski & Stack, 2007). Recent studies have shown a positive association between trait anxiety and the number of sFST (Carrillo-Díaz et al, 2020;Carrillo-Díaz et al, 2021).…”
Section: Trigger Mechanisms and Functional Aspects Of Spontaneous Fac...mentioning
confidence: 98%
See 1 more Smart Citation